FAKTOR KARAKTERISTIK DIREKSI YANG MEMPENGARUHI PRAKTIK EARNINGS MANAGEMENT PADA PERUSAHAAN SEKTOR ENERGI - Luh Gde Tiara Ary Putri; Susanto , Liana (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
This research aims to obtain empirical evidence about the influence of CEO duality, boardsize, board gender diversity, and board meetings on earnings management of energy sector companies listed on the Indonesia Stock Exchange in 2020-2022. Sample was selected using purposive sampling method and the valid sample was 39 companies. Data processing techniques using multiple regression analysis what helped by SPSS program (Statistical Product and Service Solution) for Windows released 25 and Microsoft Excel 2013. The results of this study indicate that that CEO duality, board size, and board gender diversity have a significant negative effect on earnings management. Board meetings have no influence on earnings management. The implication of this study is the need to increase CEO duality, board size and board gender diversity in a company because it can provide more effective supervision that can reduce earnings management practices.